RF and microwave oscillator design - Odyniec, Michał (Artech House microwave library., 2002)
This groundbreaking book is the first to present the state of the art in microwave oscillator design with an emphasis on new nonlinear methods. A compilation of pioneering work from experts in the field, it also provides rigorous theory and historical background. Invaluable for professionals at all levels of design expertise, this volume helps you to bridge the gap between design practice and new powerful design methods, learn all aspects of modern oscillator design and review practical designs and experimental results of fixed-frequency, high-Q, low-noise oscillators.